Fortegnelse over Meddelelser om Grønland - Andersen, Torben.; Kiær, Henning Frisch, 1893-; Bistrup, Henning August Østerberg, 1879-; Denmark. Kommissionen for videnskabelige undersøgelser i Grønland.; Denmark. Kommissionen for ledelsen af de geologiske og geografiske undersøgelser i Grønland.
Vols. for prepared by H. Bistrup; by H.F. Kiær; by Torben Andersen. Description based on: c1964. Each volume is cumulative. Kept up to date between cumulations by supplements. Mode of access: Internet. Vol. for 1918 issued by the Commission under its earlier name: Kommissionen for ledelsen af de geologiske og geografiske undersøgelser i Grønland.